"A non-person to the rest of the world": experiences of social isolation amongst severely impaired people with multiple sclerosis. Issue 16 (30th July 2020) - Freeman, Jennifer; Gorst, Terry; Gunn, Hilary; Robens, Sarah
Abstract: Purpose: To gain insight into the experiences of, and potential solutions to, social isolation amongst severely impaired people with multiple sclerosis. Methods: A phenomenological research approach using face-to-face, in-depth semi-structured, audio-recorded interviews. Data were transcribed and analyzed thematically. Results: Sixteen severely impaired people with multiple sclerosis were interviewed (Expanded Disability Status Scale >6.5); aged 38–72 years, nine female, time since diagnosis ranged 3–30 years). Four key themes were generated in line with the study objectives, each with further sub-themes. The themes were (1) Definitions of isolation (2) Causes of isolation (3) Impact of isolation, and (4) Potential eases of isolation. Conclusions: Data portrayed social isolation as complex and multi-factorial in its definitions, its causes, and its impact. Isolation is not just about being lonely or left on one's own, but represents a spiral of impacts. Physical deterioration can lead to reduced choice and control regarding access to, and interaction with others and society, affecting personal identity. Sometimes this leads to further self-isolation. Personalised psychosocial support, with improved ease of access, focused on helping people with severe multiple sclerosis regain a sense of self and their place in the world may ease social isolation. Implications for rehabilitation: People with severe multiple sclerosis can experience a sense of powerlessness, a lack of choice and control over daily life, leading to changes in self-identity and social isolation. Peoples' experiences are very personal, and any approach to help deal with social isolation needs to be based in considering how to think positively about how life can be lived and how to make that work. Multiple sclerosis support groups should not be assumed to alleviate feelings of social isolation. Interventions should focus on personalized psychosocial input aimed at helping the person with multiple sclerosis regain a sense of self and their place in the world.